Alternative application of oxen power for its optimal use - Astatke, A.; Temesgen, M. (Ethiopian Agricultural Research Organization, 1998)
Draught animals have been used in Ethiopia since the third millennium B.C. It has been confined to land preparation and seed covering using the traditional implement 'maresha', pulled mainly by a pair of oxen under a ridged neck yoke. Even though research to replace the 'maresha' and to develop multi purpose use of animal power have been carried in different parts of the country, adoption has been slow until recent years where changes in tillage practices/ implements are becoming visible in some areas of the country. Employing draught animals for alternative animal powered technologies is not yet practiced by Ethiopian farmers at large. The diversified use of draught animals offers an opportunity for optimising the large energy source at hand, especially during the off season period.